An eHealth ecosystem for stepped and early psychosocial care in advanced lung cancer: Rationale and protocol for a randomized control trial - Cristian Ochoa-Arnedo; Alejandra Arizu-Onassis; Joan C. Medina; Aida Flix-Valle; Laura Ciria-Suarez; Darío Gómez-Fernández; Arnau Souto-Sampera; Isabel Brao; Ramon Palmero; Ernest Nadal; Jesús González-Barboteo; Maria Serra-Blasco (Internet Interventions, 2023)
Background: Receiving a diagnosis of lung cancer is an emotional event, not least because it is usually diagnosed at advanced stages with limited life expectancy. Although evidence-based educational, emotional, and social interventions exist, they reach few patients and usually when it is too late. Objective: This project will be carried out in a comprehensive center for cancer care and health research, aiming to study the efficacy, costs, and utility of an eHealth ecosystem to meet the psychosocial needs of patients with advanced lung cancer. Method: We will enroll 76 patients with advanced lung cancer into an eHealth ecosystem of stepped and personalized psychosocial care for 9 months. These patients will be compared with another 76 receiving usual care in a non-inferiority randomized controlled trial. The following main outcomes will be measured every 3 months: emotional distress, spirituality, demoralization, quality of life, and medication adherence. Secondary outcomes will include symptomatology, health education, cost-utility analyses, usability and satisfaction with the platform, and time to detect emotional needs and provide care. Baseline differences between groups will be measured with the Student t-test or chi-square test, as appropriate. We will then compare the main outcomes between groups over time using multilevel linear models, report effect sizes (Hedges' g), and assess non-inferiority. The cost-utility of both interventions will be considered in terms of quality adjusted life years and quality of life given the costs of providing each treatment. Discussion: This randomized controlled trial should provide new evidence on the efficacy and cost-utility of an eHealth ecosystem to deliver personalized and timely psychosocial care to patients with advanced lung cancer. Trial registration: ClinicalTrials.gov ID “NCT05497973”.